A factorial experimental design approach to obtain defect-rich black TiO2 for photocatalytic dye degradation. (February 2022) - Saensook, Saran; Sirisuk, Akawat
Abstract: Black titanium dioxide was synthesized from sol-gel TiO2 by a chemical reduction method using solid-state NaBH4 for use in photocatalytic degradation of methyl orange dye under both UV and visible light irradiations. A 2 × 2 × 3 factorial experimental design with two replicates was used to assess the significance of (A) calcination temperature, (B) calcination time, and (C) molar ratio of NaBH4 to TiO2 used. Black titanium dioxide that was calcined at 500 °C for 10 h, and with a molar ratio of NaBH4 to TiO2 of 1:1 exhibited the highest removal percentage of methyl orange under both UV and visible light (82.17% and 71.92%, respectively) because it contained the largest amount of surface defects (Ti 3+ sites and oxygen vacancies) as suggested by XPS evidences. The surface defects acted as an electron trap and retarded the electron-hole recombination. Furthermore, the band gap energy of black TiO2 catalyst became narrower, enabling degradation under visible light. Statistical analysis indicated that out of the three main effects Factor C had the biggest impact on the photocatalytic activity. The analysis also revealed significant interactions between the amount of NaBH4 used and either calcination time or temperature. Graphical abstract: Unlabelled Image Highlights: Black TiO2 was synthesized by chemical reduction with solid-state NaBH4 . TiO2 surface defect was engineered by varying the preparation parameters. NaBH4 amount had the greatest impact on black TiO2 surface defects. Phase transition of TiO2 proceeded from anatase through brookite, and then to rutile. The best activity under visible light was only 15% lower than that under UV light.